Movement and Energy in the Debate between John Philiponus and Proclus on the Eternity of the World - Roussev, Rossen (Forum Theologicum Sardicense, 2025)
Rossen Roussev, Movement and Energy in the Debate between John Philiponus and Proclus on the Eternity of the World. The main topic of this text is the late-antique debate between the Christian philosopher John Philoponus and the pagan philosopher Proclus concerning the eternity of the world. Central to our examination is the meaning of the notion of κινησις (movement or motion) in their metaphysical systems, particularly as it relates to the Aristotelian distinction between κινησις and ἐνεργεια (activity or actuality). Proclus attempts to prove that if there were a time when the world did not exist, the Creator must have undergone some kind of alteration when He proceeded to create the world. Conversely, Philoponus argues that the actualization of God’s capacity to create the world is not an instance of alteration or movement but, according to Aristotle (De anima II.5), a perfect activity (ἐνεργεια τελεια). In his argumentation, Philoponus rehabilitates Aristotelian ontology, preferring it over the Platonic he-nology favored by Proclus.